Baumann, Carl Oral HIstory Interview Part 3 - Baumann, Carl (My University, 2009)
Part 3 of an oral history interview with Carl Baumann, facilities manager at the Synchrotron Radiation Center. Conducted by Eric Verbeten.
Keywords: Synchrotron, Baumann